Comparative Examination of Audio-Visual Rhythmic Processing in Birds and Humans. - Hagmann, Carl. (2017)
Abstract: Rhythms occur in nature in multiple sensory modalities and across variable time scales. Humans most commonly conceive of rhythms as occurring in the auditory modality, but we are sensitive to visual rhythms as well. Recent studies have found that auditory and motor networks in the brains of vocal learning animals are tightly connected (Patel, 2008). Such connectivity may enable the processing of stimuli that occur in a metric, beat-based structure, providing the framework for rhythm processing and production. If rhythmic processing is the result of vocal learning, animals that produce and mimic vocalizations should process rhythms similarly. If, instead, this is the result of phylogeny, mammals and birds should process rhythms differently. In order to evaluate these hypotheses, I trained and tested three species, humans, starlings, and pigeons, in a two-alternative forced choice tempo discrimination. The vocal learning starlings and humans exhibited many similar behaviors in the auditory modality, including sensitivity to beat onset and stimulus type organization. The birds processed visual rhythms similarly, showing behavior consistent with a combination of timing and beat-based processing. Tests of multimodal sequences revealed auditory dominance in vocal learners and visual dominance in non-vocal learners. Overall, results suggest vocal learning ability enables beat-based processing in audition, but not necessarily vision.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Psychology.; Advisor: Robert Cook.; Committee: Holly Taylor, Michael Romero, and Christopher Sturdy.; Keywords: Psychology, Animal behavior, and Cognitive psychology.